Sonographic Evaluation of Renal Changes among Drug-dependent and Drug-naive Adult Patients with Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome in Kano, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) remains a major challenge globally. HIVassociated nephropathy is the third most common cause of endstage renal failure and more prevalent among AfricanAmericans with HIV compared with other races.Aims:This study evaluated sonographic renal changes in drugdependent and drugnaive patients with HIV/AIDS in Kano, Nigeria.Materials and Methods:A prospective and comparative study involving 190 each of drugdependent and drugnaïve patients were conducted. Renal sonography was performed using digital ultrasonic diagnostic imaging system, equipped with a 3.5 MHz curvilinear transducer.Statistical analysis used:An independent ttest and Mann–Whitney Utest were used to compare the renal volume and mean rank of the renal parenchymal echogenicity between drugdependent and drugnaïve patients. Statistical significance was considered atP< 0.05.Results:The mean values of the CD4 counts were 573.20 ± 222.441 cells/mm3 for drugdependent and 252.43 ± 215.22 cells/mm3 for drugnaïve patients. The drugdependent and drugnaïve patients had mean right renal volumes of 118.12 ± 27.75 cm3 and 128.48 ± 37.73 cm3, whereas the left renal volumes were 114.84 ± 24.14 cm3 and 123.35 ± 28.22 cm3, respectively. The drugdependent patients had 6.3% and 4.7% increased renal parenchymal echogenicity on the right and left, whereas the drugsnaïve patients had 45.3% and 43.7%, respectively. There was a statistically significant difference in the right and left renal volume between drugdependent and drugnaïve patients (P= 0.003 andP= 0.002). There was a significant statistical difference in the right and left renal parenchymal echogenicity between drugdependent and drugnaïve patients (P= 0.00).Conclusions:There was a significant statistical difference in the renal volume and parenchymal echogenicity between drugdependent and drugnaïve patients.